Raspberry fliperama: protótipo de fliperama utilizando Android embarcado e Raspberry Pi 4 - Amazonas, Lorena Bastos (Brasil, 2024)
Arcade machines, which provide a fun and memorable entertainment experience, were extremely popular in past decades. Recreating these machines offers developers and enthusiasts the opportunity to relive the magic of classic games while integrating technological innovations. This work presents the initial stage of developing an arcade machine prototype, with the goal of creating an authentic classic arcade game experience with a modern and accessible approach. For this, the Raspberry Pi 4 was used in combination with the versatility of the Android system. The proposed model was developed through hardware configuration, adaptation of Android for the arcade environment, selection and implementation of emulators, and programming of physical buttons for direct interaction with the games. This approach contributes to the field of embedded systems and digital entertainment, highlighting the potential of Raspberry Pi and Android beyond their conventional applications.